Implementation of Guidance nuanced Learning Model in Islamic Based High School - El Fiah, Rifda; Bahri, Saiful (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research was conducted based on the problems that often arise in formal education learning. This problem has an impact on learning achievement results obtained by students. This research was conducted at MAN 1 Bandar Lampung. The purpose of this study was to determine the feasibility of the instructional model nuanced guidance data collection techniques using expert rating scale and user rating scale. The results of this study indicate that the nuanced learning model meets the achievement of student learning outcomes in MAN 1 Bandar Lampung, by developing students' knowledge and skills in the form of soft skills and hard skills. Guidance nuanced learning model design consists of learning process planning standards, learning process implementation standards, learning process outcome standards, and learning process control standards.